Oklusi Vena Sentral Retina: Tinjauan Pustaka - Ni Putu Ayu Reza Dhiyantari; Listya Dyah Rihardini (DiscoverSys Inc., 2020)
Introduction: Central retinal vein occlusion is vascular eye disease commonly found at ophthalmologist daily practice and also responsible for a large percentage of blindness and eye morbidity. Early diagnosis and prompt treatment may elaborate the disease and slow down disease progression.Methods: Literature review was carried out, where studies were identified through searching the PubMed, Google Scholar and Proquest database using the keywords: â€œcentral retinal vein occlusionâ€, â€œanti-VEGFâ€, â€œintraocular corticosteroidâ€, â€œretinal imagingâ€, â€œmacular oedemaâ€. Inclusion criteria include any reviews on CRVO. Exclusion criteria was reviews which were published more than 10 years ago. From 75 reviewed journals, 55 journals were included. The literatures were then analysed systematically based on the results of previous studies.Results: CRVO can be diagnosed clinically based on anamnesis, general physical examination to evaluate risk factors related to the disease and also based on routine ophthalmologic examination. Advanced imaging modalities are useful mainly to evaluate severity of the disease, to choose treatment modalities and also to evaluate disease response to therapy. CRVO management has two main goals, namely (1) to identify major risk factor underlying the disease and control it, (2) to diagnose sight threatening complications of CRVO, such as macular oedema and neovascularisation and to manage them.Â Conclusion: Current CRVO treatment modalities includes anti-VEGF and corticosteroid implants have been extensively studied in big clinical trials and already proven clinically to treat CRVO related macular oedema.Â Pendahuluan: Oklusi vena sentral mata (central retinal vein occlusion/CRVO) merupakan penyakit vaskular mata yang sering dijumpai pada praktek sehari-hari dan bertanggung jawab atas sejumlah kebutaan dan morbiditas pada mata sehingga diagnosis dini dan penatalaksanaan yang tepat dapat meningkatkan keberhasilan terapi dan mencegah komplikasi lebih lanjutMetode: Metodologi penulisan yang digunakan adalah tinjauan pustaka. Sumber literatur terdiri dari jurnal-jurnal yang relevan dari search engine PubMed, Google Scholar dan Proquest. Kata kunci yang digunakan adalah â€œcentral retinal vein occlusionâ€, â€œanti-VEGFâ€, â€œkortikosteroid intraocularâ€, â€œpencitraan retinaâ€, â€œedema makulaâ€. Kriteria inklusi adalah semua tinjauan mengenai CRVO. Kriteria eksklusi adalah literatur yang diterbitkan lebih dari 10 tahun terakhir. Dari 75 jurnal yang ditinjau, 55 ditemukan cocok sebagai referensi untuk makalah ini. Informasi yang dikumpulkan dicatat dan dianalisis untuk validitas dan reliabilitas, ditafsirkan dan disusun menjadi satu kajian literatur ilmiah.Hasil: Diagnosis CRVO dapat ditegakkan secara klinis berdasarkan anamnesis, pemeriksaan fisik umum, serta pemeriksaan ophthalmologis rutin. Pemeriksaan pencitraan penunjang dibutuhkan terutama untuk menilai derajat keparahan penyakit, mempertimbangkan tindakan atau pengobatan, serta berguna dalam menilai respon terapi. Penatalaksanaan CRVO memiliki dua tujuan utama yaitu mengidentifikasi dan mengontrol faktor risiko mayor yang mencetuskan CRVO serta mendiagnosis dan menangani komplikasi yang mengancam penglihatan, terutama edema makula dan neovaskularisasi.Kesimpulan: Penatalaksanaan CRVO saat ini sudah mengalami perkembangan yang pesat dengan banyaknya modalitas baru termasuk anti-VEGF dan implant kortikosteroid yang telah terbukti secara klinis mampu mengobati edema makula terkait CRVO